Universal Credit in Northern Ireland: what will its impact be, and what are the challenges? - Roantree, Barra (Institute for Fiscal Studies, 2013)
This is the first of two reports examining welfare reform and poverty in Northern Ireland, funded through a research call from OFMdFM in their remit as the department with policy responsibility for equality and social need in Northern Ireland. A subsequent report will produce projections of poverty rates for children and working age adults in Northern Ireland from 2010 to 2020 and investigate how these are affected by tax and benefit reforms, particularly Universal Credit.  A major reform to the welfare and tax credit system, integrating six of the seven main means-tested welfare benefits and in-work tax credits for those of working age into a single programme, to be known as Universal Credit, is set to be introduced throughout the UK. This represents a significant simplification of the benefits system as a whole.  Universal Credit will lead to a small reduction in aggregate benefit entitlements in both Northern Ireland and the UK as a whole. The total reduction in benefit entitlement as a percentage of income in Northern Ireland is slightly larger than in the UK as a whole. However, because Universal Credit is a simpler scheme, it is anticipated that take-up of means- tested support will increase as a result of its introduction, which in practice is likely to lead to higher total expenditure on benefits, despite the small reduction in entitlements.  Although benefit entitlements will fall very slightly overall in both Northern Ireland and the UK as a whole, this disguises significant winners and losers from the reform. In Northern Ireland, around 9% of families will gain and 9% of families will lose from the introduction of Universal Credit, ignoring transitional protection. Both of these figures are larger than in the UK as a whole: as Northern Ireland is a relatively low-income part of the UK, more people are entitled to means-tested support, and hence affected by reforms to means-tested benefits.  The main losers from Universal Credit’s introduction will be: low-income couples where one person is aged above the female State Pension Age (SPA) and the other is aged below, who will no longer be entitled to the more generous Pension Credit; families with significant amounts of unearned income or capital, as these are treated more harshly in the Universal Credit means test than in the means tests for tax credits; and those on Disability Living Allowance claiming the severe disability premium in means-tested benefits, which will be abolished when Universal Credit is introduced. As receipt of Disability Living Allowance is higher in Northern Ireland than in the UK as a whole, this partly explains the slightly larger reduction in benefit entitlements in Northern Ireland.  The main winners from the introduction of Universal Credit will be single- earner couples with children. This group will gain more from the introduction of Universal Credit in Northern Ireland than in the UK as a whole, mainly because gains are focused on those with lower incomes and incomes are lower on average in Northern Ireland.  By increasing support for single-earner couples while reducing support for workless families on average, Universal Credit will strengthen the incentive 6 for one member of a couple to do paid work rather than none. Universal Credit also strengthens work incentives for single people without children. However, because means-tested support is withdrawn more quickly when the second member of a couple enters work under Universal Credit, the reform weakens the incentive for both members of a couple to be in paid work rather than just one. This effect is particularly acute in Northern Ireland, as lower average earnings levels mean that a greater proportion of single-earner couples are entitled to means-tested support, meaning that those not in paid work who have a partner in paid work are more likely to face withdrawal of Universal Credit if they were to enter paid work.  By replacing a jumble of overlapping means tests with a single one, Universal Credit will go some way to ensuring overall effective tax rates cannot rise too high. Thus, some those who face the weakest incentives to increase their earnings under the current system will see their incentives strengthened. However, those previously not entitled to means-tested support who will become entitled to Universal Credit (mainly single-earners in couples with children) and those in two-earner couples tend to see weaker incentives to earn more.  Two of the main advantages of Universal Credit, then, are that it simplifies the benefits system and rationalises work incentives. However, these benefits could be undermined by the decision to leave support for local taxes (Council Tax in Great Britain and domestic rates in Northern Ireland) outside Universal Credit. As domestic rates in Northern Ireland are lower on average than Council Tax in Great Britain, support for local taxation is a correspondingly smaller component of the overall benefit system in Northern Ireland, and so this issue is less important in Northern Ireland than in the rest of the UK. Nevertheless, keeping support for domestic rates separate from Universal Credit will definitely make the overall benefits system more complicated than it could be, and could lead to the reintroduction of the very high overall withdrawal rates that Universal Credit was supposed to eliminate. How much this happens in practice will depend on decisions made by the Northern Ireland Executive surrounding the design of the proposed rate rebate replacement scheme.  The introduction of Universal Credit also raises issues around the administration of rate rebates. Currently, more than 70% of claimants of the rates component of Housing Benefit are ‘passported’ to a full rebate through receipt of other benefits that are being abolished when Universal Credit is introduced. There is no obvious alternative passport in Universal Credit that could be used to identify these people, and if they all had to go through a full means test to receive support, the burden on both claimants and administrators would increase substantially. Ways around this problem include merging the administration of Universal Credit and rate rebates, allowing claimants to claim both with the same form, or transferring information on Universal Credit claims to the appropriate authority responsible for the administration for rate rebates so that claimants would not have to submit the same information twice.  Similar issues arise around other non-social security benefits that use a passport based on receipt of other benefits to identify who is eligible. The introduction of Universal Credit offers an opportunity for the Northern Ireland Executive to consider the rationale for providing benefits in kind rather than in cash and, if these benefits should continue to be provided, whether their provision should be means tested or offered universally. For those benefits that it was decided to retain as means-tested benefits in kind, the most obvious solution would be to give these benefits only to families with incomes below a certain threshold. This would, however, create ‘cliff edges’ that would make some people worse off after a pay rise. A longer-term solution would be to allow claimants to choose which benefits in kind they wish to receive, and make a deduction against that claimant’s Universal Credit award which would depend on their income. This would be more administratively complex, but would avoid the ‘cliff edges’ inherent in alternative approaches.  In short, the UK Government and Northern Ireland Executive have taken a welcome big and radical step forward by proposing the introduction of Universal Credit. But many of the advantages it will bring could be undermined by the decision to keep support for local taxes separate from Universal Credit. Decisions to be made by the Northern Ireland Executive around the design of a rate rebate replacement scheme and other non-social security benefits will therefore be crucial in determining the extent to which these benefits are realised.
PUBLISHED
Keywords: Inclusive Society